Preferences and consumer habits related to bread in the centre of Portugal. Issue 3 (9th May 2016) - Guiné, Raquel; Matos, Mariana; Henriques, Carla; Correia, Paula
Abstract : Purpose: Bread is one of the most consumed foods in the world, and its main function is to provide nutrients and energy for the body. Thus, the purpose of this paper was to raise awareness about the consumption habits of bread and consumer preferences in the region of Viseu (centre of Portugal), assessing the extent to which the preferences and consumption habits differ based on individual variables. Design/methodology/approach: The study was conducted by means of a questionnaire by direct interviewing. The questionnaire included sections aimed at gathering information about demographics, consumption habits and preferences related to bread. The sample consisted of 500 consented respondents. Findings: The results showed significant differences between genders regarding the type of bread eaten: women consumed less wheat bread (52 per cent against 62 per cent; p = 0.029) and less unsalted bread (0.3 per cent against 3 per cent; p = 0.023), but more whole bread (25 per cent against 11 per cent; p < 0.001) and more bread with cereal grains (23 per cent against 11 per cent; p = 0.001), thus revealing a trend for a nutritionally more adequate choice. Accordingly, women valued more the composition of the bread when purchasing it ( p < 0.001). It was also observed a trend for a lower consumption of wheat bread among classes with more advanced studies (47 per cent on university graduates against 60 per cent on nongraduates; p = 0.004). Originality/value: This work is innovative because it was the first time the preferences and consuming habits of a sample of Portuguese population regarding bread were accessed, altogether. The results hereby obtained may be of importance both to understand the nutritional importance of bread in the diet of the Portuguese and also for the industry and manufacturers to better correspond to the buying preferences.